Current situation of women's mental health in Peru - Sanchez Piscoya, Susan Guadalupe (2021)
This work starts from the importance of mental health in Peruvian women, especially victims of violence (physical, psychological, sexual) and in vulnerable situations (women abandoned in mental institutions).In order to know the current situation of the mental health of women in Peru, we have studied the national regulations, the implemented model, the budget designated for its compliance, and the results of epidemiological, statistical and supervisory studies. We are convinced of the importance of mental health care for women and their environment, as well as the importance of awareness actions, promotion, prevention and treatment of mental health of the State together with other sectors, with active participation of the community, that allow the social reintegration of the person, in order to develop ourselves in a society that takes care of their mental health and that of their family.